Tagging re-booted!: imagining the potential of victim-oriented electronic monitoring - Paterson, Craig (Probation journal, 2017)
Electronic monitoring (EM) technologies or ‘tagging’, as the ankle bracelet is known, have been subject to much experimentation across the criminal justice landscape, yet there remains a good deal of conjecture concerning the purpose and subsequent effectiveness of these technologies. This article calls for renewed consideration of both the potential and pitfalls of radio frequency (RF) and global positioning by satellite (GPS) EM technologies and provides a victim-oriented perspective on future developments in EM. The author proposes further interrogation of the penal assumptions that underpin thinking about the use of EM as well as analysis of recent police experimentation with the technology. The article concludes with a call for a clear and strong probation voice in the renewed debates about EM that can guide and support ethical and effective policy and practice.